Screening for depression and anxiety disorder in children with headache - Sang Mi Lee; Jung-Rim Yoon; Yoon Young Yi; Soyong Eom; Joon Soo Lee; Heung Dong Kim; Keun-Ah Cheon; Hoon-Chul Kang (Korean Pediatric Society, 2015)
PurposeThe purpose of this study was to investigate the importance of initial screening tests for depression and anxiety disorders in children with headache. In addition, this study evaluated whether the Children's Depression Inventory (CDI) and Revised Children's Manifest Anxiety Scale (RCMAS) are suitable for screening symptoms of depression and anxiety.MethodsA retrospective chart review was conducted of 720 children aged 7-17 years who had visited a pediatric neurology clinic for headaches and were referred to a pediatric psychiatric clinic for psychiatric symptoms from January 2010 to December 2011. All patients completed the CDI and RCMAS. Among them, charts of patients with clinically significant total scores (cutoff>15) for psychiatric symptoms, as defined by the CDI and RCMAS scoring scales, were reviewed.ResultsNineteen patients had headaches and clinically significant total scores for psychiatric symptoms. The mean age at headache diagnosis was 11.7 years, and 57% were male. Mean duration of headache was 11.5 months. Two point eight percent of the patients were diagnosed with psychiatric disorders including major depression (1.7%), generalized anxiety disorder (1.1%), and bipolar disorder (0.1%). Four patients (0.6%) were diagnosed with attention deficit/hyperactivity disorder (ADHD). Total mean CDI and RCMAS scores of patients referred to the psychiatric clinic were 18.8 and 22.2, respectively. There was no correlation between CDI or RCMAS total scores and headache frequency, duration, or severity.ConclusionWe recommend that all patients with headache should be screened for depression and anxiety by CDI and RCMAS scores.